A Capacity Planning through Discrete Event Simulation - Arief Suharko (Universitas Mercu Buana, 2020)
The capacity planning serves an important role in strategic decisions involving production facilities. While there are many publications made on capacity planning, most of the models created tend to restrict their applications in real-world due to some initial assumptions being made and/or the run-time execution of the models that may be prohibitive. The objective of this paper is to explore the model construction for in-plant truck movement in a cement company that is based on building a discrete-event simulation one so that the planning may be sufficiently robust while the amount of time for constructing the model and the run-time still serve practical purposes. The model then is used to examine the effects of shifting bottlenecking and thus, allows users to identify critical resources for the production process. The results show that such a model provides the directions and aids for the management to make the strategic decisions.